Analysis of genetic relationships in the breeding material of Prunus armeniaca L. from the collection of the Mountain Botanical Garden, Dagestan - D. M. Anatov; I. I. Suprun; I. V. Stepanov; R. M. Osmanov; S. V. Tokmakov (Труды по прикладной ботанике, генетике и селекции)
Background. Dagestan boasts a long tradition of apricot cultivation that resulted in a unique gene pool of this fruit tree. However, the potential of local apricot cultivars for breeding still remains poorly investigated. This fact validates the need for further research into apricot genetic resources in Dagestan.Materials and methods. The local breeding material of apricot (23 forms and 5 cultivars) underwent genetic evaluation. For convenience, all accessions were divided into 4 groups according to the origin of cvs. ‘Krasnoshchekiy’, ‘Krymskiy Medunets’, ‘Shalakh’, and ‘Bukhara’. Their genetic diversity was analyzed using 11 SSR markers. Polymorphism of SSR markers varied 2 to 10 alleles per locus (on average, 5 alleles per locus). The effective number of alleles (Ne) and the Shannon Diversity Index (I) showed low values for the set of accessions, which is typical for seedlings with shared parental forms in their pedigrees. The differences in Ne and I values between the most contrasting groups were insignificant: Ne = 2.719 and I = 1.085 for the Shalakh group versus Ne = 2.014 and I = 0.782 for the Krasnoshchekiy group.Results. A comprehensive study of the apricot collection showed greater numbers of heterozygotes in hybrid seedlings than the expected values, attesting to large genetic distances between the pairs of parents selected for crosses. The highest heterozygosity was observed in the seedlings from the crosses ‘Krymskiy Medunets’ × ‘Krasnoshchekiy’, ‘Krasnoshchekiy’ × ‘Krymskiy Medunets’, and ‘Krymskiy Medunets’ × ‘Khonobakh’.Conclusion. Clustering the accessions with the principal coordinates analysis and Bayesian analysis on the basis of their genotyping data made it possible to identify general patterns in the distribution of cultivars and seedlings, namely the concentration of seedlings next to their maternal parents. Two genotypes attributed to cv. ‘Bukhara’ were found to have different genetic origin.